"MONITORS FORMATION IN NIEATI": PERCEPTION AND PERSPECTIVE CONCERNING THEORETICAL SUPPORT FOR THE WORK WITH ELDERLY (Fiep Bulletin - online, 2014)
Nowadays some scientific researches have proved the importance of constant and guided practice in the life quality matenance and betterment, to supply autonomy (the most basic necessity) and well-being to everybody. Then there is the "Nucleo Integrado de Estudos e Apoio à Terceira Idade" (NIEATI) with its research/extension projects. This study propose the teaching and research, having as corpus 23 Physical Education students, who want to work with elderly, developing physical activities for this people. With some aims, we desire: -To prepare, with the students, some bases of theoretical sustentation to the actions development, with activities which characterize real teaching proposals, with the human movement pedagogical aim; - To decompose in two parts (pre and post-tests) how the students of our study face this part of the population that is increasing and composing a demand of work and - To characterize the students through data like age and semester, besides their knowledge about elderly, the oldness and its consequences. The identification has indicated the majority is among 18 and 24 years old and study the three first semesters. About the questionnaire, we asked 6 definition words. In the pre-test, 22 indicated some concepts about all of them. The majority has considered the advices, the videos and the contents well elaborated, achieving their doubts, 70 % (16) has considered very good, 26%(6) has considered good and 4%(1) has considered regular. We could conclude our experience was valorous, and we intend to continue this work in each semester, by students' solicitation.
Keywords: Academic Formation; Physical Education Elderly